OP56 Modelling Future Coronary Heart Disease Mortality to 2030 in the British Isles. (10th September 2013) - Hughes, J; Kabir, Z; Hotchkiss, J W; Bennett, K; Kee, F; Leyland, A H; Davies, C A; Bandosz, P; Guzman-Castillo, M; O'Flaherty, M; Capewell, S; Critchley, J
Abstract : Background: Despite rapidly declining coronary heart disease (CHD) mortality rates over the last two decades, CHD mortality rates in the British Isles are still amongst the highest in Europe. Greater risk factor reductions have been achieved in many other countries in Europe and beyond. This study aimed to use a modelling approach to assess the potential impact of alternative future risk factor scenarios relating to smoking and physical activity levels, dietary salt and saturated fat intakes on future CHD mortality in three countries: Northern Ireland (NI), Republic of Ireland (RoI) and Scotland. Methods: CHD mortality models previously developed and validated in each country were extended to predict potential reductions in CHD mortality from 2010 (baseline year) to 2030. For each country, using risk factor data from recent surveys as a baseline, we modelled alternative future risk factor scenarios: Absolute decreases in (i) smoking prevalence and (ii) physical inactivity rates of up to 15% by 2030; (iii) relative decreases in dietary salt intake of up to 30% by 2030 & (iv) relative decreases in% energy from dietary saturated fat of up to 6% by 2030 (replacing by polyunsaturated fats). Sensitivity analyses were then conducted. Results: Projected populations by 2030 (adults aged 25-84) were 1.3, 3.9 and 3.9 million in NI, RoI and Scotland respectively. By 2030: assuming continuing declines in mortality: 15% absolute reductions in smoking could decrease CHD deaths by 6–8% (approximately 40, 130 and 210 fewer deaths In NI, RoI and Scotland respectively). 15% absolute declines in physical inactivity levels might decrease CHD deaths by 4% (approximately 30, 90 and 90 fewer deaths respectively). Relative reductions in salt intake of 30% could decrease CHD deaths by 3–4% (approximately 25, 75 and 110 fewer deaths respectively) and 6% in saturated fat intake might decrease CHD deaths by some 9–10% (approximately 65, 170 and 265 fewer deaths In NI, RoI and Scotland respectively). These projections remained stable under a wide range of sensitivity analyses. Conclusion: Modest and feasible reductions in four CHD risk factors (which have already been achieved elsewhere) could translate into substantial reductions in future CHD deaths. More aggressive polices are therefore needed in the British Isles to control tobacco, promote healthy food and increase physical activity.